Volatile biomarkers from human melanoma cells - Kwak, Jae; Gallagher, Michelle; Ozdener, Mehmet Hakan; Wysocki, Charles J.; Goldsmith, Brett R.; Isamah, Amaka; Faranda, Adam; Fakharzadeh, Steven S.; Herlyn, Meenhard; Johnson, A.T. Charlie; Preti, George (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2013)
•VOC profiles of melanoma and normal melanocytes cultured in vitro were examined.•SPME, GC/MS and single-stranded DNA-coated nanotube sensors were employed.•Uniquely different VOC profiles emanate from melanoma cells and normal melanocytes.•Qualitative and quantitative differences were found in different cells.•Monitoring of melanoma VOCs has potential as a useful screening methodology. Dogs can identify, by olfaction, melanoma on the skin of patients or melanoma samples hidden on healthy subjects, suggesting that volatile organic compounds (VOCs) from melanoma differ from those of normal skin. Studies employing gas chromatography–mass spectrometry (GC–MS) and gas sensors reported that melanoma-related VOCs differed from VOCs from normal skin sources. However, the identities of the VOCs that discriminate melanoma from normal skin were either unknown or likely derived from exogenous sources. We employed solid-phase micro-extraction, GC–MS and single-stranded DNA-coated nanotube (DNACNT) sensors to examine VOCs from melanoma and normal melanocytes. GC–MS revealed dozens of VOCs, but further analyses focused on compounds most likely of endogenous origin. Several compounds differed between cancer and normal cells, e.g., isoamyl alcohol was higher in melanoma cells than in normal melanocytes but isovaleric acid was lower in melanoma cells. These two compounds share the same precursor, viz., leucine. Melanoma cells produce dimethyldi- and trisulfide, compounds not detected in VOCs from normal melanocytes. Furthermore, analyses of the total volatile metabolome from both melanoma cells and normal melanocytes by DNACNT sensors, coupled with the GC–MS results, demonstrate clear differences between these cell systems. Consequently, monitoring of melanoma VOCs has potential as a useful screening methodology.